2021
DOI: 10.1186/s13244-021-00972-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy CT angiography reveals high prevalence of perfusion defects unrelated to pulmonary embolism in COVID-19 lesions

Abstract: Background Lung perfusion defects (PDs) have been described in COVID-19 using dual-energy computed tomography pulmonary angiography (DE-CTPA). We assessed the prevalence and characteristics of PDs in COVID-19 patients with suspected pulmonary embolism (PE) and negative CTPA. Methods This retrospective study included COVID-19 and non-COVID-19 pneumonia groups of patients with DE-CTPA negative for PE. Two radiologists rated the presence of PD within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…One hypothesis could be that greater attention was paid to the risk of PE, which might have resulted in a more inclusive indication for CTPA, as already reported [ 22 ]. An overdiagnosis of PE when there were perfusion defects unrelated to PE in dual energy CT angiography is also a possible explanation [ 23 ]. The potential overdiagnosis bias should be considered alongside a potential underdiagnosis bias, which may have occurred both in non-COVID-19 patients and in less severe non-ICU COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis could be that greater attention was paid to the risk of PE, which might have resulted in a more inclusive indication for CTPA, as already reported [ 22 ]. An overdiagnosis of PE when there were perfusion defects unrelated to PE in dual energy CT angiography is also a possible explanation [ 23 ]. The potential overdiagnosis bias should be considered alongside a potential underdiagnosis bias, which may have occurred both in non-COVID-19 patients and in less severe non-ICU COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, no PE or pulmonary hypertension was found in this patient. The PBV Z eff maps show normal perfusion with an average PBV value of 33 [27,37] ml/100 g in the left lung and 32 [19,46] ml/100 g in the right lung. In comparison, the iodine material images of this subject show a much higher signal in the left lung (6.7 [5.8, 7.6] mg/ml) than the right lung (3.0 [1.8, 4.2] mg/ml, p < 0.001).…”
Section: Resultsmentioning
confidence: 94%
“…In addition, as shown by the human subject results in this work, lung regions with consolidations and GGOs can generate a higher PBV iodine signal relative to the normally aerated lung regions.In fact,data published in multiple prior studies support the existence of this effect. [37][38][39] For example, in a fast kV switching DECT study of patients with COVID-19 pneumonia and suspected PE, two of the three showcases demonstrated higher iodine material image signal in the consolidation regions than the normally aerated parenchyma regions: one case shows a I value of 6.053 mg/ml in the consolidation, compared to 0.723 mg/ml in the normally aerated region. 37 In another dual-source DECT-based study of patients with GGOs, two of the three showcases demonstrated higher a I signals in the GGO regions than normally aerated regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations